Creation of Adhyatsa Dance Clothing - Deni, Gustu Rahma (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The Adhyatsa dance is a work of choreography created by Hana Medita. The work was inspired by the art of banteng. Bantengan art is one of the traditional arts that is particularly well-known among the people of East Java. The character of Bantengan is derived from the symbol of the bull, which represents the people who are characterised by strength, courage and protection. The objective of this research is to ascertain the influence of Bantengan art on the form of the Adhyatsa dance dress. The research method employed is the Double Diamond Model Method. The method comprises four stages: discovery, definition, development, and delivery. The outcome of this dance attire is employed in the Adhyatsa dance performance, where the garments are designed to be comfortable and facilitate unrestricted movement during the dance. The clothing in this dance work is presented in a different version from the original, yet still embodies the concept of bantengan and has been adapted to suit the character of the dancers in this Adhyatsa dance work.